Room temperature liquid metals for flexible alkali metal‐chalcogen batteries - Long Ren; Bin‐Wei Zhang (Exploration, 2022)
Abstract Flexibility has become a certain trend in the development of secondary batteries to meet the requirements of wide portability and applicability. On account of their intrinsic high energy density, flexible alkali metal‐chalcogen batteries are attracting increasing interest. Although great advances have been made in promoting the electrochemical performance of metal‐S or metal‐Se batteries, explorations on flexible chalcogen‐based batteries are still limited. Extensive and rational use of soft materials for electrodes is the main bottleneck. The re‐emergence of safe liquid metals (LMs), which provide an ideal combination of metallic and fluidic properties at room temperature, offers a fascinating paradigm for constructing flexible chalcogen batteries. They may provide dendrite‐free anodes and restrain the dissolution of polysulfides and polyselenides for cathodes. From this perspective, we elaborate on the appealing features of LMs for the construction of flexible metal‐chalcogen batteries. Recent advances on LM‐based battery are discussed, covering novel liquid alkali metals as anodes and LM‐sulfur hybrids as cathodes, with the focus placed on durable high‐energy‐density output and self‐healing flexible capability. At last, perspectives are proposed on the future development of LM‐based chalcogen batteries, and the viable strategies to meet the current challenges that are obstructing more practical flexible chalcogen batteries.